Full-time Schools in Portugal: Participation and Educational Achievement - Pedro Abrantes (Springer, 2023)
Since its implementation in 2006, Portugal's full-time schools programme led to a massive increase of curricular enrichment and family-support activities in public schools throughout the country. The literature review brings together important contributions from previous research and assessments of the full-time school programme, including results of similar programmes in other countries and particularities of the Portuguese case. The methodological design is outlined, describing the research questions as well as the variables and categories under consideration. Drawing on extensive administrative data from all public schools in the country, the analysis focuses on participation rates and their link to school location, socioeconomic context, local providers, and educational achievements. The (moderately) positive correlation between participation rates and educational success arises as a key finding, for which possible explanatory factors are discussed. The article concludes with some implications for policy-making and future research on this topic.